Method and application of organic tin compound modified PEEK material

By adding organotin compounds to PEEK materials and performing heat treatment, the problem of insufficient performance of traditional PEEK materials in high temperature, high pressure or highly corrosive media is solved, and the overall improvement of material performance is achieved.

CN119912802APending Publication Date: 2025-05-02YABANG GREEN PROCESS & NEW MATERIALS RES INST NANJING CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510049783.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

Traditional PEEK materials have insufficient performance in high temperature, high pressure or highly corrosive media, resulting in performance attenuation.

Method used

By adding an appropriate amount of organotin compound to the PEEK material and performing heat treatment, a stable structure is formed to improve the stability, heat resistance, corrosion resistance and mechanical properties of the material.

Benefits of technology

The heat resistance, corrosion resistance and mechanical properties of PEEK materials are significantly improved, so that they maintain stable performance in high temperature, high pressure or strong corrosive media.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119912802A_ABST
    Figure CN119912802A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of high polymer material modification, and discloses a method for deeply modifying a polyether-ether-ketone (PEEK) material by using an organic tin compound so as to remarkably improve the comprehensive performance of the PEEK material. By finely controlling the introduction mode and conditions of the organic tin compound, the heat resistance, corrosion resistance, mechanical strength, processability and the like of the PEEK material are successfully and comprehensively improved, and technical support is provided for wide application of the PEEK material in the field of high-end manufacturing.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of special engineering plastics, and specifically relates to a method for modifying PEEK materials by utilizing organic tin compounds and application thereof. Background Art

[0002] Polyetheretherketone (PEEK) is a high-performance special engineering plastic with excellent heat resistance, chemical stability and mechanical properties. It is widely used in aerospace, medical equipment, automobiles, electronic appliances and other fields. However, with the development of science and technology and the increase in application needs, the performance requirements for PEEK materials are becoming increasingly stringent. Traditional PEEK materials have insufficient performance in certain specific environments, such as performance degradation in high temperature, high pressure or highly corrosive media. Therefore, the development of a PEEK material with better performance and stability has important practical significance and application value. Summary of the invention

[0003] To solve the above problems, the present invention discloses an innovative application and detailed preparation method of using organic tin compounds to perform high-performance modification on PEEK materials. By adding an appropriate amount of organic tin compounds to PEEK materials, the stability, heat resistance, corrosion resistance and mechanical properties of PEEK materials can be effectively improved. By carefully selecting and proportioning organic tin compounds and combining them with a specific modification process, the present invention successfully achieves a comprehensive improvement in the performance of PEEK materials.

[0004] To achieve the above object, the technical solution of the present invention is as follows: The present invention provides a method for modifying a PEEK material using an organic tin compound, comprising the following steps: (1) Pre-treating the PEEK material; the pre-treatment includes drying, crushing, and screening to obtain a pre-treated PEEK material with a particle size D90 ≤ 150 μm; to ensure its purity and uniformity; (2) mixing the organic tin compound with the pretreated PEEK material to obtain a mixture; (3) The mixture is heat treated, and then cooled, cut, and polished to obtain a modified PEEK material.

[0005] During the heat treatment process, the organic tin compound chemically bonds with the PEEK material to form a stable structure.

[0006] Furthermore, in step (1), the drying temperature is 120° C. and the drying time is 180 minutes.

[0007] Furthermore, in step (2), the mixing method is one of melt blending and solution blending.

[0008] Furthermore, the temperature of melt blending is 310° C., the time of melt blending is 20 minutes, and the stirring time of solution blending is 30 minutes.

[0009] Furthermore, in step (2), the mass ratio of the organic tin compound to the pretreated PEEK material is 1:52.

[0010] Furthermore, the organic tin compound is one or more of dibutyltin and triphenyltin.

[0011] Furthermore, in step (3), in the process of modifying PEEK (polyetheretherketone) material with organic tin compound, heat treatment is a key step, which is crucial to improving the crystallinity of the material, eliminating thermal residue and internal stress, and improving the performance of the material. Preferably, the specific conditions of heat treatment are 160-320°C. The following is a supplement to the heat treatment steps and related parameter ranges within this temperature range: placing the PEEK material modified by the organic tin compound in a heat treatment device; (preheating stage) gradually increasing the temperature of the device to 160°C and maintaining it for a period of time, usually 1 to 2 hours, to ensure that the material is evenly heated; within the temperature range of 160 to 320°C, selecting an appropriate temperature for heat preservation treatment. The specific temperature depends on the desired modification effect and the thickness of the material. Generally speaking, the higher the temperature, the faster the crystallinity increases, but too high a temperature may cause the material to become brittle or form a surface oxide layer; (heat preservation stage) the heat preservation time is usually 2 to 8 hours, and the specific time depends on the selected temperature and the characteristics of the material. The longer the heat preservation time, the higher the crystallinity, but too long a heat preservation time may also cause the material performance to deteriorate. After the insulation is completed, reduce the equipment temperature at an appropriate rate. It is usually recommended to reduce it by 10~20℃ per hour until the temperature drops below room temperature.

[0012] Furthermore, in step (3), the heat treatment equipment is turned off and the material is allowed to cool naturally to room temperature. Natural cooling is performed in 20-30°C water. This step helps to eliminate thermal stress and reduce material deformation.

[0013] The present invention also provides a modified PEEK material prepared by the method described above.

[0014] The present invention also provides an application of the modified PEEK material prepared by the method described above in metal surface treatment and special engineering plastics.

[0015] The present invention introduces several high melting point organotin compounds to enhance the heat resistance of the system; in addition, the polar chemical bonds of the organotin interact with the PEEK molecular chains to form an adsorption-type film, resulting in the following performance improvements: (1) Heat resistance: The introduction of organic tin compounds significantly improves the heat resistance of PEEK materials, enabling them to maintain good performance stability in high temperature environments.

[0016] (2) Corrosion resistance: The modified PEEK material has stronger resistance to highly corrosive media, extending the service life of the material.

[0017] (3) Mechanical properties: The addition of organic tin compounds enhances the mechanical strength of PEEK materials, including tensile strength and impact toughness, and improves its reliability in practical applications.

[0018] (4) Processing performance: The modified PEEK material has better melt fluidity and formability, making it easy to process into products of various complex shapes.

[0019] By the modification method of the present invention, a PEEK material with better performance and better stability can be obtained. Specifically, the introduction of the organotin compound can significantly improve the heat resistance and corrosion resistance of the PEEK material, so that it can still maintain stable performance in high temperature, high pressure or highly corrosive media. At the same time, the organotin compound can also improve the mechanical properties of the PEEK material, such as improving tensile strength, impact toughness, etc.

[0020] In addition, the present invention can also adjust the type and amount of organic tin compounds according to specific needs to achieve customized regulation of the performance of PEEK materials. For example, in situations where higher heat resistance is required, organic tin compounds with higher heat resistance can be selected, such as appropriately increasing the amount of dioctyltin oxide added; in situations where better corrosion resistance is required, organic tin compounds with stronger corrosion resistance, such as dibutyltin oxide, can be selected and the amount of addition can be adjusted accordingly.

[0021] The PEEK material modification method of the present invention has the advantages of simple operation, low cost and significant effect, and is suitable for large-scale industrial production. The modified PEEK material has broad application prospects in the fields of aerospace, medical equipment, automobiles, electronic appliances, etc., especially in the fields with high requirements for material performance, such as applications in high temperature, high pressure or highly corrosive environments. For example, by adding 1% of dioctyltin oxide and 1.6% of dibutyltin oxide, the comprehensive performance can be improved by about 2-3%, which will show greater advantages and market potential.

[0022] The present invention achieves significant improvement and optimization of the performance of PEEK materials by introducing organic tin compounds to modify the PEEK materials, providing the possibility for its application in a wider range of fields. The modified PEEK materials are processed into automotive parts for actual application tests, and the processed parts are surface treated, such as deburring and cleaning, to ensure that the sample surface is smooth and free of impurities, and the sample numbers are marked for identification. The results show that its performance is stable and reliable, meeting the use requirements. The implementation method of the present invention is simple, effective, low-cost, and has broad market application prospects and huge economic value. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The performance comparison of PEEK material before and after modification in Example 2 is shown; Figure 2 The DSC graphs of the modified and unmodified PEEK material properties in Example 4 are shown. DETAILED DESCRIPTION

[0024] The present invention will be further explained below in conjunction with the accompanying drawings and specific embodiments. It should be understood that the following specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Example 1

[0025] Preparation of modified PEEK materials: (1) Pre-treating the PEEK material; the pre-treatment includes drying at 120° C. for 180 minutes, crushing in a jaw crusher until the particle size D90 is ≤150 μm; (2) 6 g of dibutyltin oxide and 194 g of pretreated PEEK material were melt-mixed at 310° C. for 20 minutes to obtain a mixture; (3) The mixture was heated to 300°C, maintained for 2 hours, and then naturally cooled in water at 20-30°C, cooled to room temperature, and then cut and polished to obtain a modified PEEK material.

[0026] The performance of the modified PEEK material was tested. The test standards are shown in the table. The results are shown in Table 1. The results show that its heat resistance and corrosion resistance are significantly improved compared with those before modification, and the tensile strength and impact toughness are also increased.

[0027] Table 1 Example 2

[0028] Preparation of modified PEEK materials: (1) Pre-treating the PEEK material; the pre-treatment includes vacuum drying at 80° C., crushing with a 50 mm alumina ball mill to a particle size of D90 ≤ 50 μm, and sieving; (2) 10 g of tetraoctyltin and 190 g of pretreated PEEK material were mixed and stirred in 300 g of ethanol for 30 minutes, and after evaporating the solvent, a mixture was obtained; (3) The mixture is heat treated by heating to 320°C for 2 hours, then naturally cooled in water at 20-30°C, cooled to room temperature, cut, and polished to obtain a modified PEEK material.

[0029] The modified PEEK material was subjected to performance testing. The test standards are shown in the table. The results are shown in Table 2. The results show that its heat resistance, corrosion resistance and mechanical properties are significantly improved, especially in high temperature and highly corrosive media. It shows excellent stability.

[0030] Table 2

[0031] It can be seen from the above examples that the present invention uses organic tin compounds to modify PEEK materials, which can effectively improve their performance and provide the possibility for the application of PEEK materials in a wider range of fields. At the same time, the method of the present invention is simple and easy to implement, low in cost, suitable for large-scale industrial production, and has broad market application prospects.

[0032] Experimental data and result analysis: The present invention provides some experimental data, including performance comparison data of PEEK materials before and after modification. Through in-depth analysis of these data, various properties of the modified PEEK are synchronously improved, further verifying the effectiveness and superiority of the present invention.

[0033] Example 2: Tetraoctyltin was added and the verification experiment was repeated. The performance comparison of PEEK material before and after modification is shown in Table 3 and Figure 1 shown.

[0034] Table 3 Example 3

[0035] Sample preparation: The high heat-resistant PEEK composite material is the same as Example 2 except that: In step (2), 5.7 g of dioctyl tin oxide (the amount of dioctyl tin oxide added is 3% of the mass of the PEEK resin) is added to prepare a modified PEEK material, which is then prepared into a test sample by a conventional injection molding process.

[0036] The highly corrosion-resistant PEEK composite material is the same as in Example 1 except that: In step (2), 3.8 g of dibutyltin oxide (the amount of dibutyltin oxide added is 2% of the mass of the PEEK resin) is added to prepare a modified PEEK material, which is also prepared into a test sample by a conventional injection molding process.

[0037] Control group: A pure PEEK sample without adding an organotin compound was prepared as a comparison.

[0038] Performance test and experimental results Heat resistance test: Using differential scanning calorimeter (DSC) to test the melting point of the sample (high heat resistance PEEK composite material) was 3.5°C higher than that of the control group.

[0039] Corrosion resistance test: The samples were immersed in a 3% sodium chloride solution and kept at a certain temperature (80°C) for a certain period of time (72 hours). The corrosion of the samples was then observed and recorded. The mass loss of the test samples (highly corrosion-resistant PEEK composite materials) was reduced by 0.8% compared to the control group, and there was no significant change in the surface morphology.

[0040] Experimental Results Heat resistance test results: The melting point of the high heat-resistant PEEK composite material is significantly higher than that of the control group, indicating that the addition of dioctyltin oxide effectively improves the heat resistance of PEEK.

[0041] Corrosion resistance test results: The mass loss and surface morphology change of the highly corrosion-resistant PEEK composite material in sodium chloride solution were smaller than those of the control group, indicating that the addition of dibutyltin oxide effectively improved the corrosion resistance of PEEK. Example 4

[0042] Sample preparation: The rest is the same as Example 2, except that 1% (0.9 g) of dioctyltin oxide (DOSn) and 1.6% (3.04 g) of dibutyltin oxide (DBSn) are added in step (2) to prepare a standard test sample by injection molding or extrusion process.

[0043] Performance Test: Heat resistance: The melting point of the material was determined using a differential scanning calorimeter (DSC).

[0044] Corrosion resistance: The samples were immersed in 3% sodium chloride solution at 80°C for 72 hours, and the mass loss and surface corrosion were evaluated.

[0045] Mechanical properties: Tests for tensile strength, flexural strength, and impact strength to assess the structural integrity of the material.

[0046] Experimental data and results Heat resistance: like Figure 2 As shown in the figure, the melting point of modified PEEK is 3.8℃ higher than that of unmodified PEEK, indicating that its heat resistance is significantly improved.

[0047] Corrosion resistance: After immersion in 3% sodium chloride solution for 72 hours, the corrosion mass loss of modified PEEK was relatively reduced by 4.6% compared with the corrosion mass loss of unmodified PEEK, and the degree of surface corrosion was significantly reduced.

[0048] Mechanical properties: The tensile strength, flexural strength, and impact strength of the modified PEEK increased by approximately 2%, 3%, and 2.5%, respectively, indicating that its comprehensive mechanical properties were improved.

[0049] It should be noted that the above content only illustrates the technical idea of ​​the present invention and cannot be used to limit the protection scope of the present invention. For ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications all fall within the protection scope of the claims of the present invention.

Claims

1. A method for modifying PEEK material using an organic tin compound, characterized in that: The following steps are involved: Pre-treating the PEEK material; the pre-treatment includes drying, crushing, and screening to obtain a pre-treated PEEK material with a particle size of D90≤150um; (2) mixing the organic tin compound with the pretreated PEEK material to obtain a mixture; (3) The mixture is heat treated, and then cooled, cut, and polished to obtain a modified PEEK material.

2. The method for modifying PEEK material using an organic tin compound according to claim 1, characterized in that: In step (1), the drying temperature is 120° C. and the drying time is 180 minutes.

3. The method for modifying PEEK material using an organic tin compound according to claim 1, characterized in that: In step (2), the mixing method is one of melt blending and solution blending.

4. The method for modifying PEEK material using an organic tin compound according to claim 3, characterized in that: The temperature of melt blending was 310° C., and the time of melt blending was 20 minutes; the stirring time of solution blending was 30 minutes.

5. The method for modifying PEEK material using an organic tin compound according to claim 1, characterized in that: In step (2), the mass ratio of the organic tin compound to the pretreated PEEK material is 1:

52.

6. The method for modifying PEEK material using an organic tin compound according to claim 5, characterized in that: The organic tin compound is one or more of dibutyltin and triphenyltin.

7. The method for modifying PEEK material using an organic tin compound according to claim 1, characterized in that: In step (3), in the process of modifying PEEK (polyetheretherketone) material using organic tin compounds, heat treatment is a key step, which is essential for improving the crystallinity of the material, eliminating thermal residue and internal stress, and improving the performance of the material. The specific conditions of the heat treatment are 160-320°C.

8. The method for modifying PEEK material using an organic tin compound according to claim 1, characterized in that: In step (3), turn off the heat treatment equipment and allow the material to cool naturally to room temperature. Cool naturally in 20-30℃ water.

9. A modified PEEK material prepared by the method according to any one of claims 1 to 8.

10. Application of the modified PEEK material prepared by the method according to any one of claims 1 to 8 in metal surface treatment and special engineering plastics.